Pukeko Pictures and the Kiwi DIY Spirit: Building Global Partnerships from the End of the World. (July 2019) - Potter, Anna; O'Regan, Tom
Wellington, New Zealand is a major international screen production base for movies including Peter Jackson's Lord of the Rings and The Hobbit trilogies. New Zealand production companies like Jackson's Weta Group producing content for international markets benefit from local policy settings that support such productions. In 2008, a group of long-time Jackson collaborators including Richard Taylor established Pukeko Pictures. In a small country with a deregulated media system, no dedicated public service broadcaster, and minimal supports for children's television, Pukeko is a successful, globally oriented producer of children's content. This article examines the strategies that underpin Pukeko Pictures' production portfolio, which includes the 2015 reboot Thunderbirds Are Go, and a preschool coproduction with China. The combination of dispersed production practices, local subsidies, and quality infrastructure contribute to Pukeko Pictures' success. We suggest, however, that strategic international relationships managed by Taylor are also critical to Pukeko Pictures developing a significant foothold in transnational television services.